A transferência de tecnologia na indústria brasileira de confecções: práticas usuais e recomendações para melhorias - Neves, João Victor Silva (2019)
The Brazilian textile industry has a large industrial role in the country, as it has been generating jobs and moving the economy. For the industry to become even more competitive, delivering differentiated articles in the shortest possible time, technology transfer is critical, where upgrading the industrial park makes the work environment modern and capable of producing quality and large scale. The aim of this paper is to propose a guide with steps that can be used by the textile industry, facing bed, table and bath, as well as assisting in their technology transfer procedures. A qualitative and quantitative research was carried out, aiming to achieve the objective, in which the respondents evaluated as additions to the best practices in the literature on a Likert scale from 0 to 5. To better understand technology transfer (TT), as well as its application, or the type of research used was exploratory. A data collection technique was performed by sending questionnaires to bed, table and bath companies through the Survey method. An analysis of the results made it possible to propose a 15-step set of practices as a technology transfer guide for the bed, table and bath textile industry.